2013
DOI: 10.1111/liv.12126
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the mTOR inhibitor RAD001, the dual mTOR and PI3‐kinase inhibitor BEZ235 and the PI3‐kinase inhibitor BKM120 in hepatocellular carcinoma

Abstract: In this study, BKM120 showed the strongest antitumour activity. Our findings suggest impairment of mitochondrial function as a relevant mechanism of BKM120. Moreover, combination of PI3K and mTOR inhibitors with cytotoxic agents could be promising option for non-cirrhotic HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 38 publications
7
41
0
Order By: Relevance
“…These results are in accordance with the results of Shoji et al and Oishi et al, who used commercial EC cell lines and ovarian clear cell carcinoma cell lines, respectively [17,30]. In hepatocellular carcinoma, however, Kirstein et al indicated that NVP-BKM120 has a higher antitumor activity compared to RAD001 (mTORC1 inhibitor) and NVP-BEZ235 [31].…”
Section: Discussionsupporting
confidence: 92%
“…These results are in accordance with the results of Shoji et al and Oishi et al, who used commercial EC cell lines and ovarian clear cell carcinoma cell lines, respectively [17,30]. In hepatocellular carcinoma, however, Kirstein et al indicated that NVP-BKM120 has a higher antitumor activity compared to RAD001 (mTORC1 inhibitor) and NVP-BEZ235 [31].…”
Section: Discussionsupporting
confidence: 92%
“…For everolimus it was expected that reduced mTOR activation would lead to reduced transcription of glycolytic enzymes and therefore a shift to mitochondrial respiration [23]. In contrast, we observed that everolimus inhibits mitochondrial respiration, which was not compensated by an enhanced glycolysis rate, as previously reported for hepatocellular carcinoma cells as well [24]. In human pancreatic cancer cell lines, however, everolimus treatment reduced the rate of glycolysis.…”
Section: Discussionsupporting
confidence: 75%
“…$ indicates bins containing values that were reported in literature as IC 50 > x  μM ( x =position of indicated bin). Values were extracted from refs 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47.…”
Section: Figurementioning
confidence: 99%